Isolated Attosecond Pulses Generated Directly from a Femtosecond Chirped Pulse Amplifier - Wu, Yi; Gilbertson, Steve; Khan, Sabih; Chini, Michael; Zhao, Kun; Feng, Ximao; Chang, Zenghu (Institute of Electrical and Electronics Engineers, 2010)
Using a generalized version of double optical gating, we produced single isolated attosecond pulses with 2 mJ, 25 fs driving lasers. Through attosecond streaking, we characterized isolated 160 attosecond pulses with 170 pJ pulse energy.
Keywords: Chirp modulation; Optical parametric amplifiers; Optical pulse generation